A versatile genetic toolkit for engineering Wickerhamomyces ciferrii for tetraacetyl phytosphingosine production - Lee, Seong-Rae; Kang, Jun Su; Lee, Pyung Cheon (Frontiers in Bioengineering and Biotechnology, 2025)
Wickerhamomyces ciferrii: a non-conventional yeast with significant industrial potential for tetraacetyl phytosphingosine (TAPS), remains underutilized due to the lack of a comprehensive genetic toolbox. In this study, we developed a modular genetic system tailored for Wickerhamomyces ciferrii to enable strain engineering and metabolic pathway optimization. This toolkit includes episomal plasmids incorporating multiple selectable markers, replication origins, and fluorescent reporters. Systematic evaluation of four antibiotic resistance markers demonstrated that nourseothricin, geneticin, and zeocin effectively confer resistance, whereas hygromycin B did not support selection in this host. Among three tested replication origins, 2μ and CEN6/ARS4 enabled stable episomal maintenance, whereas panARS failed to replicate. Expression analysis of six fluorescent proteins under the endogenous PGK1 promoter revealed significant variability in transcript levels, which correlated with codon adaptation index values, emphasizing the importance of codon optimization for heterologous expression. Additionally, characterization of the endogenous TDH3, PGK1, and PDA1 promoters using two highly expressed fluorescent proteins confirmed that promoter strength is largely independent of the downstream coding sequence. To demonstrate the functional application of this toolkit, we overexpressed a phosphorylation-insensitive mutant of acetyl-CoA carboxylase (ACC1S26A-S1161A), resulting in a 2.4-fold increase in TAPS production. Collectively, this study establishes a versatile genetic platform for W. ciferrii, providing a robust foundation for future synthetic biology and metabolic engineering applications.